Analisis Kinerja Keuangan Dengan Menggunakan Pendekatan Value For Money Pada PT AR Management Periode Tahun 2021-2023 - Panjaitan, Rosianna Clara; Nurrasyad, Raka Aji; Ramadhon, Satrio Cahyo; Sari, Bida (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to assess the financial performance of the AR Management work unit by applying the Value for Money approach. Analysis was carried out on the Budget Realization Report for the period 2021 to 2023. The method used was quantitative descriptive by comparing ratios based on Value for Money, namely Economic, Effectiveness and Efficiency ratios. The data used in this research is secondary data originating from budget realization report documents for 2021 to 2023. The results of the ratio calculation show that the AR Management work unit budget realization report for these years recorded an Economic value < 100, an Effectiveness value > 100, and an Efficiency value of <100, which indicates that the realization of the AR Management budget in 2021 to 2023 meets the economic, efficient and effective elements.